The effect of music on stress and anxiety of dental patients - Naderzadeh, Hamideh; Peymani, Javid; Naseri, Mandana (Journal of Dental School, 2019)
Objectives Dental anxiety often leads to avoidance of patients which may result in significant deterioration of oral health. Non‐pharmacological interventions such as music are increasingly used in dental care. The purpose of this study was to investigate the effect of relaxing music on the stress and anxiety level of dental patients. Methods In this study, 40 adult patients were randomly divided into two groups of music and control (no intervention). Each group included 10 females and 10 males. Subjects in the music group listened to relaxation music throughout their dental procedure while the control group did not. Pre- and post-tests were performed using the Spielberger's State-Trait Anxiety Inventory (STAI) and Hari’s stress questionnaire in both groups. Results There were no significant differences between the two groups for baseline data. The mean age of patients in the music and control groups was 37.70±9.29 years and 39.05±5.36 years, respectively. Comparison of moderated means in the intervention and control groups showed that listening to relaxation music caused a reduction in the mean scores of STAI (x=7.746, SE=416, P<0.05) and stress (x=7.746, SE=2.103, P<0.01) in the intervention compared with the control group. Conclusion This study indicated that relaxing music can decrease the state anxiety and stress of dental patients